The Effect of Workload on Employee Performance with Work Stress as a Mediating Variable in Satuan Polisi Pamong Praja Kabupaten Bekasi - Tiara Rahmawati,; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
Performing field tasks that achieve targets can lead to workload due to the feeling of responsibility experienced, which can affect employee performance. This study aims to explore the impact of workload on employee performance, with job stress as a mediating variable. The study used a quantitative descriptive approach and was conducted at the Bekasi Regency Civil Service Police Unit. The population consisted of 253 employees, with a sample of 72 respondents selected using the slovin formula with an error rate of 10%. Data collection was carried out through questionnaire distribution and analysis using the PLS-SEM (Partial Least Square-Structural Equation Model) method with the help of SmartPLS 3.0 software. The results showed a positive and significant correlation between work pressure and employee performance, as well as between work pressure and job stress. In addition, there is a positive and significant relationship between work stress and employee performance, with work stress acting as a mediator between work pressure and employee performance.